P133 A cut above the rest – the utility of physician ultrasound guided, non-targeted, percutaneous pleural biopsy to improve diagnostic pathways. (11th November 2022) - Thayanandan, A; Gleeson, L; Sinharay, S; Turner, R; Ross, C
Abstract : Introduction and Objectives: Pleural fluid cytology is frequently non diagnostic, or just not diagnostic enough! Real-time ultrasound-guided percutaneous pleural biopsy, using an 18G cutting needle, is a minimally-invasive bed side procedure that can be performed in patients with confirmed or suspected exudative effusions, and as such could be utilised more widely and earlier in a patient's pathway. Method: This was a retrospective study reviewing records of patients who had a percutaneous pleural biopsy performed at our trust between January 2021 and June 2022 by the pleural intervention team under real-time ultrasound. All of these biopsies were non-targeted (i.e. were not directed at areas of clear pleural nodularity on imaging), and were mostly done in patients with non-diagnostic fluid results. Almost all patients had pleural fluid sampled concurrently to biopsy, even if done previously. Results: 25 patients had a pleural biopsy. In 14, fluid sampling had been previously insufficient for a diagnosis; 11 had not undergone fluid sampling prior to pleural biopsy. 19 patients had abnormal pleura identified on CT imaging (ranging from subtle smooth thickening to gross thickening with nodularity). 13 of 25 ( 52% ) patients with no prior diagnosis had a definitive diagnosis established on biopsy (cancer, n=7; tuberculosis, n=3; other, n=3), vs. 3 ( 12% ) on pleural fluid alone (cancer, n=2; TB, n=1). No patient suffered any significant complication. Conclusions: On a small sample size, percutaneous pleural biopsy had a diagnostic hit rate of 52%, compared to 12% on pleural fluid. 50% of patients with suspected malignancy had this definitively diagnosed on biopsy; these samples were sufficient for molecular genetic analysis to guide oncology management. Pleural biopsy was also more effective than fluid alone at confirming a diagnosis of TB and providing PCR and culture results. This relatively simple procedure can be utilised early in a patients diagnostic pathway to confirm a definitive diagnosis and help avoid further, resource heavy, invasive procedures that patients may not want, be fit for, or have access to. A larger prospective study is need to examine this further and identify potential biomarkers which increase the pre-test probability of a diagnostic biopsy.